2018
DOI: 10.1200/jco.2018.36.4_suppl.458
|View full text |Cite
|
Sign up to set email alerts
|

Second-line treatment of modified FOLFIRINOX or nab-paclitaxel plus gemcitabine for metastatic pancreatic adenocarcinoma.

Abstract: 458 Background: Both FOLFIRINOX (FFX) and Nab-paclitaxel plus Gemcitabine(GnP) standard treatment in first-line treatment of metastatic pancreatic adenocarcinoma (MPA). It could be of interest to use them consecutively, knowing that there is currently no standard for second-line treatments for MPA. The aim of this study was to compare second-line modified FFX (mFFX) after GnP failure with second-line GnP after mFFX failure. Methods: From January 2015 to Jul 2017, medical records were retrospectively reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Moreover, previous studies reported that median PFS and OS of second-line GnP after FFX were 2.4-6.4 and 4.6-16.2 months, respectively (Table 4) [8][9][10][11][12][13][14][15][16][17][18][19]. PFS in the present study was comparable to the previous reports, and OS in the present study was considered good.…”
Section: Discussion/conclusionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, previous studies reported that median PFS and OS of second-line GnP after FFX were 2.4-6.4 and 4.6-16.2 months, respectively (Table 4) [8][9][10][11][12][13][14][15][16][17][18][19]. PFS in the present study was comparable to the previous reports, and OS in the present study was considered good.…”
Section: Discussion/conclusionsupporting
confidence: 88%
“…On the other hand, there has been no large prospective study of second-line treatment after FFX. Only a few studies of second-line GnP after FFX have been reported [8][9][10][11][12][13][14][15][16][17][18][19]. In these reports, median PFS was 2.4-6.4 months.…”
Section: Introductionmentioning
confidence: 99%
“…6 journals.sagepub.com/home/tam A total of 11 studies assessed the DCR of gemcitabine-based chemotherapy (412 patient). 12,22,[25][26][27][28][29][30][31][32][33] Radiological response evaluation took place every 8 weeks in four studies 22,26,27,33 and in one study the median time to first disease response assessment was 8.9 weeks. 32 In the remaining investigations, time to first disease response evaluation was not stated.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…12,22,[25][26][27][28][29][30][31][32][33][34][35] Six studies were multicentric investigations 22,23,26,27,31,34 and seven were available solely as posters or electronic abstracts. 11,24,25,[29][30][31]34 S7 illustrates treatment characteristics in the selected studies. Amongst noncomparative studies, five evaluated the activity of single-agent gemcitabine [25][26][27]33,35 and eight assessed the activity of gemcitabine plus nab-paclitaxel.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation